Progress on a meta-analysis for comparing hook, bait and leader effects on target, bycatch and vulnerable fauna interactions - Casaca Santos, Catarina (2021)
This paper describes the progress of an EU Project "Evaluation of the effects of hooks’ shape & size on the catchability, yields and mortality of target and by-catch species, in the Atlantic Ocean and adjacent seas surface longline fisheries". At this stage, a meta-analysis of 36 publications totaling 55 experiments was conducted to assess effects of hook, bait, and leader type on retention and at-haulback mortality rates of swordfish, blue shark, and loggerhead sea-turtle. Using circle hooks significantly lowers retention rates of loggerhead sea-turtles and swordfish. Fish bait significantly reduces the retention of loggerhead sea-turtles but does not significantly affect the retention of swordfish or blue shark. The effects of using wire leaders could not be assessed for the loggerhead turtle and significantly increased retention of blue sharks. As for at-haulback mortality, it was significantly reduced for swordfish when using circle hooks. Fish bait increased at-haulback mortality of blue shark and was not significant for the other taxa. The effects of using wire leaders on at-haulback mortality were only possible to calculate for blue shark and were not significant.